Identification of the oleic acide ethanolamide (OEA) isomer cis-vaccenic acid ethanolamide (VEA) as a highly abundant 18:1 fatty acid ethanolamide in blood plasma from rats and humans - Röhrig, Waldemar; Waibel, Reiner; Perlwitz, Christopher; Pischetsrieder, Monika; Hoch, Tobias (Analytical and Bioanalytical Chemistry, 2016)
The endocannabinoid system is important in various physiological pathways, especially the regulation of food intake. It consists of endocannabinoids like 2-arachidonoyl-glycerol (2-AG) or the fatty acid ethanolamide archachidonoyl-ethanolamide (AEA) with binding affinity to cannabinoid receptors. Further, fatty acid ethanolamides (FAEAs) influence the endocannabinoid system without affecting cannabinoid receptors by using independent physiological pathways. Among FAEAs, oleic acid ethanolamide (OEA) gained importance because of its promising ability to reduce food intake. By ultrahigh-performance liquid chromatography–electrospray ionization–tandem mass spectrometry (UHPLC–ESI–MS/MS), we detected a chromatographically separated molecule in plasma samples from rats and humans with identical mass and fragmentation patterns as those of OEA. Via synthesis and extensive analysis of ethanolamides of different cis/trans- and position isomers of oleic acid (cis9-18:1), we could identify the unknown molecule as vaccenic acid (cis11-18:1) ethanolamide (VEA). In this study we identified VEA as the most abundant 18:1 FAEA in rat plasma and the second most abundant 18:1 FAEA in human plasma.
Keywords: OEA; VEA; fatty acid ethanolamides; endocannabinoid system; LC - MS/MS

Quantification of 24 circulating endocannabinoids, endocannabinoid-related compounds, and their phospholipid precursors in human plasma by UHPLC-MS/MS. - Röhrig, Waldemar; Achenbach, Susanne; Deutsch, Birgit; Pischetsrieder, Monika (Journal of Lipid Research, 2019)
Endocannabinoids and endocannabinoid-related compounds (ERCs) are involved in many physiological processes. They are released on demand from phosphoinositide and N-acylphosphatidyl ethanolamine (NAPE) precursors and comprise 2-monoacylglycerols (2-MGs) and FA ethanolamides (FEAs). Despite the abundance of advanced quantitative methods, however, their determined concentrations in blood plasma are inconsistent because 2-MGs and FEAs undergo artifactual de novo formation, chemical isomerization, and degradation during sample collection and storage. For a comprehensive survey of these compounds in blood and plasma, we have developed and validated an ultra-HPLC-MS/MS method to quantify 24 endocannabinoids, ERCs, and their phospholipid precursors. Immediate acidification of EDTA-blood to pH 5.8 blocked artifactual FEA formation for at least 4 h on ice. The 2-MGs were stabilized after plasma harvest with 0.5 M potassium thiocyanate at pH 4.7. FEA and MG plasma concentrations in six healthy volunteers ranged between 0.04-3.48 and 0.63-6.18 ng/ml, respectively. Interestingly, only 1-5% of circulating FEAs were present in their free form, while the majority was bound to NAPEs. Similarly, 97% of 2-arachidonoylglycerol (2-AG) was bound to a potential phosphoinositide pool. The herein-described stabilization and extraction methods may now be used to reliably and comprehensively quantify endocannabinoids, ERCs, and their phospholipid precursors in clinical studies.
Keywords: fatty acid ethanolamide; 2-arachidonoylglycerol; 2-monoacylglycerol; N-acylphosphatidyl ethanolamine; phosphatidyl ethanolamine; arachidonoyl phosphoinositid; Orlistat; blood; lipases; phospholipases

Tracing metabolite profiles in human milk: Studies on the odorant 1,8-cineole transferred into breast milk after oral intake. - Kirsch, Frauke; Horst, Kathie; Röhrig, Waldemar; Rychlik, Michael; Büttner, Andrea (Metabolomics, 2013)
The transfer of certain substances from the maternal diet or medication into breast milk has been known for many years. There is currently also an increasing interest in odorants in human milk and their potential influence on the breastfed child. Nevertheless, metabolic products originating from bioconversion of odorants within the maternal organism have hitherto not been considered. Breastfed children may take in xenobiotic compounds that are transferred unmodified into human milk, but also their metabolic derivatives. Metabolic activation is a crucial point for evaluation of both positive and negative biological effects, thus it is important to understand the basic principles of metabolism in human milk. The present study investigated metabolite profiles of the odorant 1,8-cineole (eucalyptol) in human milk after lactating mothers ingested a non-prescription pharmaceutical (Soledum®) containing this substance. Ten different metabolites were identified, five of which have been previously described in humans and other mammals (α2-hydroxy-1,8-cineole, β2-hydroxy-1,8-cineole, α3-hydroxy-1,8-cineole, 7-hydroxy-1,8-cineole, 9-hydroxy-1,8-cineole). Three of the metabolites have hitherto only been found in microorganisms and insects (2-oxo-1,8-cineole, 3-oxo-1,8-cineole, 2,3-dehydro-1,8-cineole) and the derivatives α2,3-epoxy-1,8-cineole and 4-hydroxy-1,8-cineole have never before been identified as metabolites of 1,8-cineole. Metabolism profiles showed large inter- and intra-individual differences and were strongly related to sampling time. Identification and relative quantification of the metabolites were accomplished by gas chromatography–mass spectrometry (GC–MS) after preparation of the human milk extracts by solvent assisted flavour evaporation (SAFE). Synthesised reference substances were used to confirm the chemical identity of the detected substances.<br

Tracing metabolite profiles in human milk: Studies on the odorant 1,8-cineole transferred into breast milk after oral intake - Kirsch, Frauke; Horst, Kathie; Röhrig, Waldemar; Rychlik, Michael; Büttner, Andrea (Metabolomics, 2013)
The transfer of certain substances from the maternal diet or medication into breast milk has been known for many years. There is currently also an increasing interest in odorants in human milk and their potential influence on the breastfed child. Nevertheless, metabolic products originating from bioconversion of odorants within the maternal organism have hitherto not been considered. Breastfed children may take in xenobiotic compounds that are transferred unmodified into human milk, but also their metabolic derivatives. Metabolic activation is a crucial point for evaluation of both positive and negative biological effects, thus it is important to understand the basic principles of metabolism in human milk. The present study investigated metabolite profiles of the odorant 1,8-cineole (eucalyptol) in human milk after lactating mothers ingested a non-prescription pharmaceutical (Soledum®) containing this substance. Ten different metabolites were identified, five of which have been previously described in humans and other mammals (α2-hydroxy-1,8-cineole, β2-hydroxy-1,8-cineole, α3-hydroxy-1,8-cineole, 7-hydroxy-1,8-cineole, 9-hydroxy-1,8-cineole). Three of the metabolites have hitherto only been found in microorganisms and insects (2-oxo-1,8-cineole, 3-oxo-1,8-cineole, 2,3-dehydro-1,8-cineole) and the derivatives α2,3-epoxy-1,8-cineole and 4-hydroxy-1,8-cineole have never before been identified as metabolites of 1,8-cineole. Metabolism profiles showed large inter- and intra-individual differences and were strongly related to sampling time. Identification and relative quantification of the metabolites were accomplished by gas chromatography-mass spectrometry (GC-MS) after preparation of the human milk extracts by solvent assisted flavour evaporation (SAFE). Synthesised reference substances were used to confirm the chemical identity of the detected substances. © 2012 Springer Science+Business Media New York.
UnivIS-Import:2015-03-09:Pub.2013.nat.dchph.llmch.tracin
Keywords: 1; 8-Cineole; Cytochrome P450; Gas-chromatography mass-spectrometry; Human milk; Hydroxy-cineole; Metabolites

Vaccensäure-Ethanolamid (VEA) - Ein neues endogenes Fettsäure-Ethanolamid im Endocannabinoid-System von Ratte und Mensch - Röhrig, Waldemar; et al. (Lebensmittelchemie, 2015)
UnivIS-Import:2017-12-18:Pub.2015.nat.dchph.llmch.vaccen